The Content of the Use of Innovative Pedagogical Technologies in the Educational Process - Abdurashitovna, Mamajonova Guluzro (European Journal of Life Safety and Stability (2660-9630), 2021)
the article provides information about the content of the use of innovative pedagogical technologies in the educational process, methods of its application in practice.